The Effectiveness of Mobile Learning Apps in Enhancing Vocabulary Acquisition Among Uzbek EFL Learners - Norpoʻlatova Nozima Yusufxon qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
In the digital age, mobile learning has become an integral part of the educational landscape. The proliferation of smartphones and mobile applications has brought new opportunities for learners, particularly in the field of language acquisition. For Uzbek students learning English as a Foreign Language (EFL), mobile learning apps offer a flexible, engaging, and accessible platform for enhancing their vocabulary acquisition. This article explores the effectiveness of mobile learning apps in improving vocabulary acquisition among Uzbek EFL learners, examining both the advantages and challenges of using these tools in language learning.